Insect-Assisted Biodegradation of Waste Plastics for Enhancing Sustainable Development Goals - Umami, Muhimatul; Narakusumo, Raden Pramesa; Encilia, Encilia; Nada, Shofwatun; Amrulloh, Ilham; Agung, Achmad; Sekarwangi, Dewi (Biosaintifika: Journal of Biology & Biology Education, 2025)
The increasing use of plastic materials in daily life has led to a rise in plastic waste, contributing significantly to environmental pollution. This study aims to analyze the characteristics of insects that contribute to the eco-friendly degradation of plastic waste and to evaluate the rate of plastic waste degradation and the waste reduction index (WRI) achieved through insect larvae. The research uses a Randomized Factorial Design, investigating plastics such as styrofoam blocks, low-density polyethylene, polyurethane, polystyrene, and a control. The parameters examined include insect characteristics, larval length and weight, degradation rate, and WRI. Both Zophobas atratus and Tenebrio molitor exhibit the potential for the bioconversion of plastic waste. The weight of T. molitor larvae ranges from 0.07-0.09g, while Z. atratus larvae weigh between 0.51 and 0.60g. The WRI is directly proportional to the reduction rate, with higher reduction rates corresponding to higher WRI values. The results showed that the control using Z. atratus and T. molitor larvae achieved the highest WRI values among all treatments. Among the plastic types studied, styrofoam blocks showed the highest WRI value, indicating that a feeding rate of 1g of plastic per larva per day is optimal for efficiently reducing plastic waste. This supports circular economy initiatives for companies developing insect-based proteins for food, feed, and natural products while advancing sustainable development goals.